Testimonial Narratives of Muslim Tausug: Against Militarization in Sulu (1972-1974) - Salomon, Elgin Glenn R. (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2022)
In order to provide a counter history to the predominate, monochromatic, and polarizing historiography of Martial Law in the Philippines, this article investigates the use of testimonial narratives from Muslim Tausug witnesses and survivors during the early years of militarization of Sulu province in the southern Philippines (1972–1974). It focuses on the narratives of war and violence which have been silenced and subjugated, as well as the role of identities and culture in the articulation of the conflict. Their testimonies offer a different perspective on the marginalization of Muslim Mindanao under the repressive era of Ferdinand Marcos’ Martial Law. This article contributes to the study of Islam in the Philippines and Bangsamoro by exploring the ways in which Tausug Muslims use their religion to air their grievances and to fight against oppression. They were able to embrace Islam as their framework for emancipation because of their roots in postcolonial experience.